[P053] Contrast-enhanced digital mammography on commercial systems: an optimization study. (August 2018) - Contillo, Adriano; Taibi, Angelo
Abstract : Purpose: We introduce a novel algorithm for dual energy (DE) subtraction proposed in[1, 2], based on an iterative procedure for taking into account the intrinsic polychromaticity of conventional X-ray tubes. The result is an improvement of background cancellation with respect to the currently available DE systems. The algorithm was applied to a set of DE radiographs of a dedicated anthropomorphic phantom embedding small agglomerates of contrast medium (iodine), acquired with a commercial mammography system. Methods: The employed anthropomorphic phantom, specifically designed for DE applications, is a polymethyl methacrylate (PMMA) box of parallelepipedal shape. It contains a large number of PMMA spheres of different diameters, embedded in paraffin wax. Moreover, it embeds a system of cavities that can be filled with iodine solutions of various concentrations. The phantom was imaged with X-ray beams of low energy (29 ± 2 kV) and high energy (47 ± 2 kV), generated by a commercial mammography unit with a tungsten anode and additional filtrations of rhodium (low energy) and copper (high energy). Results: We achieved an almost complete cancellation of the background texture, resulting in an enhanced visibility of the iodine details. Such result was achieved with lower exposures than the values typical of diagnostic practice. We noticed no significant dependence of the image quality on the particular choice of beam energies. Conclusions: The implementation of the novel subtraction algorithm on a commercial unit allowed an effective background cancellation with a reduced amount of delivered dose. Such result was largely independent of the imaging parameters, which is an indication of robustness of the algorithm. In conclusion, the proposed algorithm paves the way to an improvement of the diagnostic effectiveness of DE imaging.